UPAYA MENINGKATKAN KEAKTIFAN PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA TINGKAT LANJUT MENGGUNAKAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) - Nurazizah Makkawaru (Jurnal Education, 2025)
This research is a type of classroom action research (PTK) which aims to increase students' active learning in advanced mathematics through the application of the Teaching at the Right Level (TaRL) approach. The subjects in this research were class XI students. 4 at UPT SMA Negeri 13 Makassar consisting of 34 students. The instruments used to collect data include observation sheets on learning implementation, student activity observation sheets. Data analysis was carried out using quantitative descriptive techniques using percentages. The results of the research show that the application of the TaRL learning approach is able to increase students' advanced mathematics learning skills. This can be seen from the percentage increase in student activity results from cycle I to cycle II, where the increase includes all indicators. And overall it increased by 8.7%.